Electrochemical Behavior of Some Cinchona Alkaloids Using Screen-Printed Electrodes - Tonino Caruso; Laura Palombi (Sensors)
An effective deposition of a cinchonine layer on a platinum metal surface can be easily achieved through the cathodic reduction of a cinchonine hydrochloride methanolic solution at a controlled potential of −220 mV vs. the silver standard electrode (SSE). A coated screen-printed platinum electrode has proven to be suitable for cinchonine determination in water, urine, and serum at µg L−1 concentration levels using differential pulse voltammetry in a phosphate buffer solution (pH 7.0). The limits of detection (LOD) and quantitation (LOQ) were 0.6 µg L−1 and 1.8 µg L−1, respectively.